Influence of Buckwheat Seed Fractions on Dough and Baking Performance of Wheat Bread - Ionica Coţovanu; Silvia Mironeasa (Agronomy, 2022)
The study was conducted to determine the influence of buckwheat fractions (BF) on the physicochemical characteristics of wheat flour (WF), dough rheology, and bread quality parameters. Buckwheat seeds’ fractionation influenced the microstructure and molecular conformation depending on the particle size (PS). The protein content of the WF–BF improved when the medium PS was added and decreased for large and small PS. Lipids and ash increased with the increase in BF amount in all samples in comparison with the control. Dough tenacity increased with BF addition, being higher than in WF dough only when large PS were added, while samples with medium and small PS presented a lower tenacity in comparison with the control. Dough extensibility decreased significantly in all samples when BF increased, as follows: M ˃ S ˃ L. Dough viscoelastic moduli increased proportionally when adding large PS, while the addition of medium PS (5–15%) and small PS decreased it. Bread firmness, springiness, and gumminess rose proportionally with the addition level. Bread volume decreased when BF increased, and medium PS had a good influence on this parameter. Bread porosity and elasticity presented higher values than for the control bread, but these decreased when the BF amount increased. Flour and bread crust and crumb color parameters were also influenced by different fractions of BF addition.